2015
DOI: 10.17129/botsci.214
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variation of flowering and vegetative morphological traits along the distribution for the endemic species Yucca capensis (Agavaceae)

Abstract: Phenotypic variation across the geographic range of a species depends upon genetic differences within and between populations as well as environmental heterogeneity. Estimating the variation in morphological and reproductive traits and determining the infl uence of abiotic factors on the expression of phenotype is particularly important in endemic species as a means of inferring their response to different environmental scenarios. This study analyzes the interpopulation variation in fl oral and vegetative trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 16 publications
1
11
0
3
Order By: Relevance
“…We found that a set of characters are highly variable. However, a third alternative is that our observed robustness or variability is not due to natural variation or phenotypic plasticity, but rather the age of the plant, as was previously seen in Yucca capensis seen in (Arteaga et al 2015).…”
Section: Discussionmentioning
confidence: 91%
“…We found that a set of characters are highly variable. However, a third alternative is that our observed robustness or variability is not due to natural variation or phenotypic plasticity, but rather the age of the plant, as was previously seen in Yucca capensis seen in (Arteaga et al 2015).…”
Section: Discussionmentioning
confidence: 91%
“…Plants of Y. valida flower between April and July (Turner et al, 1995;personal observation). In turn, populations of Y. capensis mainly grow in a remnant of tropical deciduous forest along the mountains located in the southern part of the Baja California Peninsula (Lenz, 1998;De la Luz et al, 2012), and consist of groups of less than 15 individuals separated by considerable distances (Lenz, 1998;Arteaga et al, 2015). Flowering of Y. capensis, in part, is determined by rainfall, with the boom during September and October (Lenz, 1998;Arteaga et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, populations of Y. capensis mainly grow in a remnant of tropical deciduous forest along the mountains located in the southern part of the Baja California Peninsula ( Lenz, 1998 ; De la Luz et al, 2012 ), and consist of groups of less than 15 individuals separated by considerable distances ( Lenz, 1998 ; Arteaga et al, 2015 ). Flowering of Y. capensis , in part, is determined by rainfall, with the boom during September and October ( Lenz, 1998 ; Arteaga et al, 2015 ). These two sister Yucca species are pollinated by the same yucca moth, Tegeticula baja Pellmyr ( Pellmyr et al, 2007 , 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…The genetic variation in a population is caused by multiple factors such as geneflow, genetic drift, mutation, reproductive biology, phylogenetic relatedness, and natural selection [20][21][22]. However, contemporary processes like environmental changes due to demographic factors may also play roles in genetic variation [23]. Several studies have found relationships between morphological variation and geographic locations [24,25].…”
Section: Introductionmentioning
confidence: 99%